'Into the custody of the Serjeant at Arms': inducing parliamentary attendance in Dublin and Westminster, 1690–1859. (4th May 2018) - Wolfe, Eugene L.
ABSTRACT: Parliamentary attendance could be quite problematic before the advent of modern political parties. For more than a century after the Glorious Revolution both the English/British and Irish Houses of Commons sought to address this challenge by ordering the Serjeant at Arms to take into custody hundreds of absent Members of Parliament (MPs). The extraordinary expedient of turning parliament into a prison, albeit of the softest variety imaginable, did not solve the attendance problem. On the contrary, it became considerably worse after both Houses adopted new rules for adjudicating controverted elections in the late eighteenth century. Nevertheless, the willingness to employ this distasteful and rather ineffective weapon quickly dwindled. The last arrest order for unauthorized absence came in 1859, 112 years before the final occasion on which Westminster was forced to adjourn business for want of MPs.